Applicability of electronic sphygmomanometer use in high-altitude areas according to the AAMI/ESH/ISO collaboration statement - Liu, Xueting; Ye, Runyu; Zhang, Xin; Huang, Wen; Sun, Lirong; Huo, Xingwei; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2024)
Objective Mercury sphygmomanometer (MS) has now been less and less used and no new devices have been manufactured (according to Minamata convention 2013). The application of the electronic sphygmomanometer (ES) in clinical practice has become increasingly common. However, reliable evidence for the use of the ES in high-altitude areas remains scarce. The purpose of this study was to validate the applicability of the ES in high altitude areas. Methods In Luhuo County, Sichuan Province, China, 3,400 m above the sea level, two trained physicians measured the blood pressure (BP) of participants using both the mercury sphygmomanometer and the ES. Pearson correlation analysis and paired T-test, respectively, were used to compare the correlation and the difference between the BP values measured by the two devices. The applicability of the ES in high-altitude areas was evaluated according to the validation standards of the 2018 Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Collaboration Statement. Results In this study, 257 participants were included. There was a strong correlation between BP values measured by the two devices, with correlation coefficients for systolic blood pressure (SBP) and diastolic blood pressure (DBP) of 0.97 and 0.93, respectively. Compared with the MS, the ES tended to measure the subjects' DBP (76.21 ± 13.29 mmHg vs. 76.53 ± 14.07 mmHg; P = 0.557) accurately, but overestimate the SBP of the subjects (123.32 ± 22.25 mmHg vs. 121.34 ± 22.88 mmHg; P < 0.001) to some extent. The consistency of the two devices in the classification of normal BP, prehypertension, and hypertension was 88.9%, 80.7%, and 89.2%, respectively. Conclusions In general, the utilization of ES at 3,400 m altitude successfully met the validation standards of the AAMI/ESH/ISO Collaboration Statement. The use of ES can be recommended at a high altitude, including up to 3,400 m. In addition, because the ES tended to overestimate SBP, we speculate that it may need to be calibrated in high-altitude areas.